Lubricity of ethanol–diesel blends – Study with the HFRR method. (15th November 2017) - Kuszewski, Hubert; Jaworski, Artur; Ustrzycki, Adam
Highlights: Lubricity tests using the HFRR method for the ethanol–diesel blends were presented. Microscopic photographs of the test ball wear scars were presented and discussed. The results of the lubricity tests were referenced to the standard requirements. Abstract: Due to increasing fuel consumption in various industries, especially in road transport, interest in increasing the market participation of renewable fuels is growing. One such fuel is ethanol. The raw materials for its production include sugar beets, sugar cane, potatoes and many other starch-containing plants. Ethanol can be used as a pure fuel in positive-ignition engines that have undergone relatively minor technical modifications. However, in compression-ignition engines, due to factors such as a very low cetane number and lubricity, ethanol cannot be used as a pure fuel. Therefore, increasing attention is being paid to fuel consisting of blends of diesel fuel with certain concentrations of ethanol. Diesel fuel containing up to 15% (v/v) ethanol is sometimes referred to as e-diesel or oxygenated diesel. In this paper, the lubricity of blends of conventional diesel fuel and ethanol, with ethanol content up to 14% (v/v), were tested. The HFRR ( High-Frequency Reciprocating Rig ) method was used for the research, which is a normative method of determining the lubricity of diesel fuel. For individual fuel samples, microscopic photographs of wear scar caused on test balls, along with the designation of areas that have been considered when measuring the diameters of wear scars, were presented. The obtained values of WSD ( Wear Scar Diameter ) were compared to the regulatory requirements for diesel fuels. Further measurements of kinematic viscosity, density and water content were conducted for individual fuel samples. The results showed that in the range of up to 14% (v/v), the proportion of ethanol in diesel fuel causes hardly any changes to its lubricity as determined by HFRR, and in addition, diesel fuel with up to 14% (v/v) added ethanol still meets the standard requirements in terms of lubricity.